An ordered intermetallic compound catalyst, its preparation method and use
Patent Information
- Application Number
- CN202611416837.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-30
AI Technical Summary
在此情形下,采用传统的直接退火方法难以将受热力学制约的金属体系转化为有序金属间化合物
[0016]本申请提供了一种制备有序金属间化合物催化剂的普适性方法,创新地通过氮介导方法来合成有序的金属间化合物催化剂,首先通过氮化处理得到有序的金属间氮化物中间体,再通过氢气和氮反应生成氨气并逸出,低温脱除有序金属间氮化物结构中的氮原子,同时在动力学层面维持有序金属间结构不变,最终制备得到纯相有序金属间化合物催化剂;在逆水煤气变换反应中具有优异的催化活性和选择性,当反应温度为400℃时能达到平衡转化率,且具有良好的稳定性。该制备工艺简单,操作简便,易于重复,具有良好的工业化应用前景。
Smart Images

Figure CN122999255A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of catalyst technology, and in particular to an ordered intermetallic compound catalyst, its preparation method, and its application. Background Technology
[0002] Intermetallic compound catalysts, with their well-defined crystal structures and regular surface atomic arrangements, endow the materials with unique geometric configurations and electronic properties, thus exhibiting significant advantages in catalytic activity, selectivity, and stability, and have broad application prospects in energy, catalysis, and materials fields.
[0003] However, the controllable synthesis of intermetallic compounds remains a serious challenge due to the differences in the intrinsic physicochemical properties of different metals. One fundamental factor stems from thermodynamic limitations. Specifically, for many metal systems, the formation energy of the ordered alloy phase is higher than, and sometimes even positively higher than, the formation energy of the corresponding disordered solid solution phase. This makes the system thermodynamically more inclined to form disordered solid solutions or phase-separated structures rather than ordered intermetallic compounds. In this case, traditional direct annealing methods are insufficient to transform thermodynamically constrained metal systems into ordered intermetallic compounds. Moreover, even if the formation of the ordered phase is thermodynamically feasible, its ordering process usually requires high-temperature annealing to overcome the kinetic energy barrier of atomic ordering, which often leads to particle sintering and a decrease in dispersion.
[0004] Therefore, developing a universal synthetic strategy that enables the controllable construction of thermodynamically favorable or even thermodynamically constrained intermetallic compounds at mild reaction temperatures is of significant research importance and application value. Summary of the Invention
[0005] In view of this, this application provides a method for synthesizing ordered intermetallic compound catalysts through a nitrogen-mediated strategy and their application. The ordered intermetallic compound catalysts exhibit excellent catalytic activity, selectivity and stability in the reverse water-gas shift reaction.
[0006] This application provides a method for preparing an ordered intermetallic compound catalyst, comprising: The first metal salt and the second metal salt are loaded onto a carrier material, and then dried and calcined to nitride, resulting in ordered intermetallic nitrides. Ordered intermetallic nitrides were subjected to low-temperature hydrogen annealing to obtain ordered intermetallic compound catalysts. The temperature for the low-temperature hydrogen annealing is between 200°C and 600°C.
[0007] In some specific implementations, the atmosphere for the low-temperature hydrogen annealing includes hydrogen. The low-temperature hydrogen annealing time is from 0.1 h to 24 h.
[0008] In some specific implementations, the temperature of the calcination nitriding treatment is between 200°C and 1000°C; The calcination and nitriding treatment time is from 0.1 h to 24 h; The atmosphere for the calcination and nitriding treatment includes one or both of hydrogen and ammonia.
[0009] In some specific implementations, the first metal salt and the second metal salt are each independently one or more of the following: nitrate of metal ions, chloride of metal ions, sulfate of metal ions, acetylacetone of metal ions, and acetate of metal ions.
[0010] In some specific implementations, the metal ions in the first metal salt and the metal ions in the second metal salt are each independently selected from one or more of nickel ions, cobalt ions, iron ions, copper ions, zinc ions, platinum ions, indium ions, silver ions, cadmium ions, aluminum ions, or magnesium ions.
[0011] In some specific implementations, the molar ratio of metal ions in the first metal salt to the second metal salt is (1-5):1.
[0012] In some specific implementations, the carrier material includes one or more of carbon nitride, commercial carbon black, activated carbon, graphene, carbon nanotubes, aluminum oxide, silicon dioxide, cerium dioxide, zirconium dioxide, and titanium dioxide.
[0013] This application also provides an ordered intermetallic compound catalyst, prepared according to the preparation method described above.
[0014] This application also provides a method for converting carbon dioxide and hydrogen into carbon monoxide, comprising: Carbon dioxide and hydrogen are reacted with water gas in the presence of a catalyst to produce carbon monoxide. The catalyst is an ordered intermetallic compound as described above or an ordered intermetallic compound catalyst prepared according to the preparation method described above.
[0015] In some specific implementations, the temperature of the reverse water gas reaction is 200°C to 600°C; The pressure of the reverse water gas reaction is 0.5 bar to 10 bar; The volume ratio of carbon dioxide to hydrogen is 1:(1-5).
[0016] This application provides a universal method for preparing ordered intermetallic compound catalysts. It innovatively synthesizes ordered intermetallic compound catalysts via a nitrogen-mediated method. First, an ordered intermetallic nitride intermediate is obtained through nitridation. Then, ammonia is generated and released through the reaction of hydrogen and nitrogen. Nitrogen atoms in the ordered intermetallic nitride structure are removed at low temperature while maintaining the ordered intermetallic structure at the kinetic level, ultimately yielding a pure-phase ordered intermetallic compound catalyst. This catalyst exhibits excellent catalytic activity and selectivity in the reverse water-gas shift reaction, reaching equilibrium conversion at 400℃ and demonstrating good stability. The preparation process is simple, easy to operate, and easily reproducible, showing promising prospects for industrial application. Attached Figure Description
[0017] Figure 1 The X-ray diffraction patterns are those of the nickel-copper nitride and nickel-copper ordered alloy prepared in Example 1 of this application. Figure 2 This is an atomic-level aberration electron microscope image of the nickel-cadmium alloy prepared by the nitrogen-mediated method in Example 3 of this application; Figure 3 This is an atomic-level spherical aberration electron microscope image of the nickel-indium alloy prepared by the nitrogen-mediated method in Example 4 of this application; Figure 4 This is an atomic-level aberration electron microscope image of the carbon black-supported nickel-copper alloy prepared by the nitrogen-mediated method in Example 5 of this application; Figure 5 This is an atomic-level aberration electron microscope image of the carbon black-supported nickel-copper alloy prepared by the nitrogen-mediated method in Example 6 of this application; Figure 6 This is an atomic-level aberration electron microscope image of the nickel-copper alloy prepared by the nitrogen-mediated method in Example 1 of this application; Figure 7 An atomic-level spherical aberration electron microscope image of the nickel-copper alloy prepared by the direct annealing method in Comparative Example 1 of this application; Figure 8 The activity diagrams are of the nickel-copper ordered alloy catalyst prepared in Example 1 of this application and the nickel-copper disordered alloy catalyst prepared in Comparative Example 1. Figure 9 This is an atomic-level aberration electron microscope image of the nickel-silver alloy prepared by the nitrogen-mediated method in Example 2 of this application; Figure 10 This is an atomic-level spherical aberration electron microscope image of the nickel-silver alloy prepared by the direct annealing method in Comparative Example 2 of this application; Figure 11 The activity diagrams are for the nickel-silver ordered alloy catalyst prepared in Example 2 of this application and the nickel-silver disordered alloy catalyst prepared in Comparative Example 2. Detailed Implementation
[0018] It should be understood that the expression “one or more of…” individually includes each of the objects described after the expression, as well as various different combinations of two or more of the described objects, unless otherwise understood from the context and usage. The expression “and / or” combined with three or more described objects should be understood to have the same meaning, unless otherwise understood from the context.
[0019] The terms “including,” “having,” or “containing,” including the use of their grammatical synonyms, should generally be understood as open-ended and non-restrictive, for example, not excluding other unstated elements or steps, unless otherwise specifically stated or understood from the context.
[0020] It should be understood that the order of steps or the sequence of actions is not important as long as this application remains operational. Furthermore, two or more steps or actions can be performed simultaneously.
[0021] The use of any and all instances or exemplary language such as “e.g.” or “include” in this document is intended merely to better illustrate the application and does not constitute a limitation on the scope of the application. No language in this specification should be construed as indicating that any unclaimed element is essential to the practice of this application.
[0022] Furthermore, the numerical ranges and parameters used to define this application are approximate values, and the relevant values in the specific embodiments have been presented as precisely as possible. However, any numerical value inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise explicitly stated, it should be understood that all ranges, quantities, values, and percentages used in this disclosure are modified with the word "approximately." Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a specific value or range.
[0023] This application provides a method for preparing an ordered intermetallic compound catalyst, comprising: The first metal salt and the second metal salt are loaded onto a carrier material, and then dried and calcined to nitride, resulting in ordered intermetallic nitrides. Ordered intermetallic nitrides were subjected to low-temperature hydrogen annealing to obtain ordered intermetallic compound catalysts. The temperature for the low-temperature hydrogen annealing is between 200°C and 600°C.
[0024] This application uses a first metal salt and a second metal salt combined with a support material as raw materials. By introducing a special calcination nitriding atmosphere, ordered intermetallic nitrogen compounds are prepared. After annealing, an ordered intermetallic compound catalyst is obtained. This catalyst exhibits excellent catalytic activity and selectivity in the reaction of carbon dioxide and hydrogen to carbon monoxide, reaching equilibrium conversion at a reaction temperature of 400℃ and demonstrating good stability. The preparation process is simple, easy to operate, and easily reproducible, showing promising prospects for industrial application.
[0025] This application first mixes and dries a first metal salt, a second metal salt, and a carrier material to obtain a calcination precursor. In some specific implementations, the first metal salt includes, but is not limited to, one or more of the following: nickel nitrate, cobalt nitrate, ferric nitrate, copper nitrate, platinum nitrate, palladium nitrate, nickel chloride, cobalt chloride, ferric chloride, copper chloride, platinum chloride, palladium chloride, nickel sulfate, cobalt sulfate, ferric sulfate, copper sulfate, platinum sulfate, palladium sulfate, nickel acetylacetonate, cobalt acetylacetonate, ferric acetylacetonate, copper acetylacetonate, platinum acetylacetonate, palladium acetylacetonate, nickel acetate, cobalt acetate, ferric acetate, copper acetate, platinum acetate, and palladium acetate. This application does not have any special requirements for the selection of the first metal salt. In some specific implementations, the second metal salt includes, but is not limited to, one or more of the following: nickel nitrate, cobalt nitrate, ferric nitrate, copper nitrate, platinum nitrate, indium nitrate, silver nitrate, zinc nitrate, cadmium nitrate, aluminum nitrate, platinum nitrate, palladium nitrate, nickel chloride, cobalt chloride, ferric chloride, copper chloride, platinum chloride, indium chloride, silver chloride, zinc chloride, cadmium chloride, aluminum chloride, platinum chloride, palladium chloride, nickel sulfate, cobalt sulfate, ferric sulfate, copper sulfate, platinum sulfate, indium sulfate, silver sulfate, zinc sulfate, cadmium sulfate, aluminum sulfate, platinum sulfate, palladium sulfate, nickel acetylacetone, cobalt acetylacetone, ferric acetylacetone, copper acetylacetone, platinum acetylacetone, indium acetylacetone, silver acetylacetone, zinc acetylacetone, cadmium acetylacetone, aluminum acetylacetone, platinum acetylacetone, palladium acetylacetone, nickel acetate, cobalt acetate, ferric acetate, copper acetate, platinum acetate, indium acetate, silver acetate, zinc acetate, cadmium acetate, aluminum acetate, platinum acetate, and palladium acetate. This application does not have specific requirements regarding the selection of the second metal salt. Preferably, the first metal salt and the second metal salt are each independently one or more of nitrates, chlorides, sulfates, acetylacetones, and acetates, with nitrates being more preferred. Preferably, the first metal salt is one or more of nickel, cobalt, iron, copper, platinum, and palladium, with nickel being more preferred; the second metal salt is one or more of nickel, cobalt, iron, copper, indium, silver, zinc, cadmium, aluminum, platinum, and palladium, with copper, silver, cadmium, and indium being more preferred. In some specific implementations, the molar ratio of metal ions in the first metal salt to the second metal salt is (1-5):1, preferably 1:1, 2:1, 3:1, 4:1, or 5:1, and more preferably 3:1. In some specific implementations, the carrier material includes, but is not limited to, one or more of carbon nitride, commercial carbon black, activated carbon, graphene, carbon nanotubes, aluminum oxide, silicon dioxide, cerium dioxide, zirconium dioxide, and titanium dioxide. This application does not have special requirements for the selection of carrier material, but carbon nitride and commercial carbon black are preferred, and carbon nitride is more preferred.
[0026] This application then subjectes the calcined precursor to calcination and nitriding treatment to obtain ordered intermetallic nitrides. This application prepares ordered intermetallic compounds under specific calcination conditions, exhibiting excellent catalytic activity and selectivity in the reverse water-gas shift reaction. In some specific implementations, the atmosphere for the calcination and nitriding treatment is one or both of hydrogen and ammonia, or a mixture of ammonia and other inert gases, preferably a mixture of ammonia and hydrogen, and more preferably ammonia. In some specific implementations, the temperature for the calcination and nitriding treatment is 200°C to 1000°C, preferably 300°C to 700°C, and more preferably 400°C to 500°C; the time for the calcination and nitriding treatment is 0.1 h to 24 h, preferably 1 h to 20 h, and more preferably 5 h to 10 h. Preferably, the atmosphere for the calcination and nitriding treatment is a 10% ammonia / argon mixture, the calcination and nitriding treatment temperature is 500°C, and the calcination and nitriding treatment time is 6 h. The heating rate of the calcined precursor to the calcination nitriding treatment temperature is 2°C / min to 8°C / min, preferably 4°C / min to 6°C / min, and more preferably 5°C / min.
[0027] This application then subjectes the ordered intermetallic nitrides to low-temperature hydrogen annealing to obtain an ordered intermetallic compound catalyst. In some specific implementations, the atmosphere for the low-temperature hydrogen annealing includes hydrogen and may also include an inert gas, such as argon, nitrogen, and helium; the temperature for the low-temperature hydrogen annealing is 200°C to 600°C, preferably 300°C to 600°C, more preferably 400°C to 500°C; the time for the low-temperature hydrogen annealing is 0.1 h to 24 h, preferably 1 h to 10 h, more preferably 2 h to 5 h. Preferably, the calcination nitriding treatment atmosphere is a 10% hydrogen / argon mixture, the low-temperature hydrogen annealing temperature is 400°C, and the low-temperature hydrogen annealing time is 2 h. The low-temperature hydrogen annealing is followed by cooling. This application does not have specific requirements for the cooling method; cooling to room temperature is acceptable. When the cooling is natural cooling, the cooling time is 2 h to 24 h, preferably 2 h to 10 h, more preferably 2 h. After the calcination and nitriding treatment, the temperature is cooled to room temperature and then raised to the low-temperature hydrogen annealing temperature at a rate of 2°C / min to 8°C / min, preferably 4°C / min to 6°C / min, and more preferably 5°C / min.
[0028] This application provides a universal method for preparing ordered intermetallic compound catalysts. It innovatively synthesizes ordered intermetallic compound catalysts through the permeation-removal of bulk nitrogen atoms. These catalysts exhibit excellent catalytic activity and selectivity in the reverse water-gas shift reaction, reaching equilibrium conversion at a reaction temperature of 400℃ and demonstrating good stability. The preparation process is simple, easy to operate, and readily reproducible, showing promising prospects for industrial application.
[0029] This application also provides a method for converting carbon dioxide and hydrogen into carbon monoxide, comprising: Carbon dioxide and hydrogen are reacted with water gas in the presence of a catalyst to produce carbon monoxide. The catalyst is an ordered intermetallic compound as described above or an ordered intermetallic compound catalyst prepared according to the preparation method described above.
[0030] The temperature of the reverse water gas reaction is 200°C to 600°C, preferably 300°C to 500°C, and more preferably 400°C; the pressure of the reverse water gas reaction is 0.5 bar to 10 bar, preferably 0.5 bar to 5 bar, and more preferably 1 bar; the volume ratio of carbon dioxide to hydrogen is 1:(1-5), preferably 1:(2-4), and more preferably 1:3.
[0031] Specifically, the catalyst is placed in a quartz tube, and the quartz tube is placed on a flow-through fixed-bed reactor. The reaction atmosphere is a mixture of carbon dioxide and hydrogen. This application does not have any special requirements regarding the amount of catalyst used.
[0032] The present application is further illustrated below with reference to embodiments. The scope of protection of the present application is not limited to the following embodiments.
[0033] The reagents used in the following embodiments of this application, such as gases (carbon dioxide, hydrogen, argon, etc.) and reagents such as copper nitrate, nickel nitrate, silver nitrate, cadmium nitrate, indium nitrate, nickel chloride, copper chloride, melamine, and carbon black, were all purchased from the market.
[0034] Example 1
[0035] This embodiment provides an ordered intermetallic compound catalyst, the preparation method of which includes: 10g of melamine was weighed and placed in a crucible, covered, and placed in a muffle furnace. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined for 4 hours. After cooling to room temperature, the resulting carbon nitride material was thoroughly ground into powder for later use. 0.291g of nickel nitrate hexahydrate and 0.081g of copper nitrate trihydrate were weighed and dissolved in 1mL of deionized water to prepare a metal salt solution. 1.0g of carbon nitride powder was then weighed and added to the metal salt solution. The solution was ultrasonically dispersed at room temperature for 30 minutes and then dried in a 60℃ oven to obtain the calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under an NH3 atmosphere. After holding at this temperature for 6 hours, it was allowed to cool naturally to obtain nickel-copper nitride. Subsequently, the NH3 gas was switched to 10 vol% H2 / Ar gas, and the temperature was increased to 400℃ at a heating rate of 5℃ / min. After holding at this temperature for 2 hours, the temperature was naturally cooled to obtain an ordered nickel-copper alloy catalyst (an ordered intermetallic compound catalyst).
[0036] X-ray diffraction was used to test the nickel-copper nitride and the finally prepared nickel-copper ordered alloy catalyst. The X-ray diffraction patterns of the nickel-copper nitride and nickel-copper ordered alloy prepared in Example 1 of this application are shown below. Figure 1 As shown, the X-ray diffraction pattern of nickel-copper nitride is similar to that of standard anti-perovskite nitride (Ni3CuN). Figure 1 The X-ray diffraction pattern of the ordered nickel-copper alloy is consistent with that of the nickel-copper alloy (Ni3Cu), indicating that nitrogen infiltration into the Ni3Cu alloy forms an ordered Ni3CuN. Hydrogen treatment can further remove nitrogen atoms from the bulk phase to obtain an ordered nickel-copper alloy (ordered intermetallic compound catalyst).
[0037] Example 2
[0038] This embodiment provides an ordered intermetallic compound catalyst, the preparation method of which includes: 10g of melamine was weighed and placed in a crucible, covered, and placed in a muffle furnace. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined for 4 hours. After cooling to room temperature, the resulting carbon nitride material was thoroughly ground into powder for later use. 0.291g of nickel nitrate hexahydrate and 0.057g of silver nitrate were weighed and dissolved in 1mL of deionized water to prepare a metal salt solution. 1.0g of carbon nitride powder was then weighed and added to the metal salt solution. The solution was ultrasonically dispersed at room temperature for 30 minutes and then dried in a 60℃ oven to obtain a calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under an NH3 atmosphere. After holding at this temperature for 6 hours, it was allowed to cool naturally to obtain nickel-silver nitride. Subsequently, the NH3 gas was switched to 10 vol% H2 / Ar gas, and the temperature was increased to 400℃ at a rate of 5℃ / min. After holding at this temperature for 2 hours, it was allowed to cool naturally to obtain an ordered nickel-silver alloy catalyst.
[0039] Example 3
[0040] This embodiment provides an ordered intermetallic compound catalyst, the preparation method of which includes: 10g of melamine was weighed and placed in a crucible, covered, and placed in a muffle furnace. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined for 4 hours. After cooling to room temperature, the resulting carbon nitride material was thoroughly ground into powder for later use. 0.291g of nickel nitrate hexahydrate and 0.108g of cadmium nitrate tetrahydrate were weighed and dissolved in 1mL of deionized water to prepare a metal salt solution. 1.0g of carbon nitride powder was then weighed and added to the metal salt solution. The solution was ultrasonically dispersed at room temperature for 30 minutes and then dried in a 60℃ oven to obtain the calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under an NH3 atmosphere. After holding at this temperature for 6 hours, it was allowed to cool naturally to obtain nickel-cadmium nitride. Subsequently, the NH3 gas was switched to 10 vol% H2 / Ar gas, and the temperature was increased to 400℃ at a heating rate of 5℃ / min. After holding at this temperature for 2 hours, the temperature was naturally cooled to obtain an ordered nickel-cadmium alloy catalyst.
[0041] The final nickel-cadmium ordered alloy catalyst was analyzed using atomic-resolution aberration-corrected electron microscopy. The atomic-resolution aberration-corrected electron microscopy image of the nickel-cadmium alloy prepared by the nitrogen-mediated method in Example 3 of this application is shown below. Figure 2 As shown, the nickel-cadmium alloy catalyst prepared in Example 3 of this application exhibits an ordered distribution of nickel and cadmium atoms. This result proves that the method used in Example 3 of this application can effectively synthesize an ordered nickel-cadmium alloy catalyst.
[0042] Example 4
[0043] This embodiment provides an ordered intermetallic compound catalyst, the preparation method of which includes: 10g of melamine was weighed and placed in a crucible, covered, and placed in a muffle furnace. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined for 4 hours. After cooling to room temperature, the resulting carbon nitride material was thoroughly ground into powder for later use. 0.291g of nickel nitrate hexahydrate and 0.124g of indium nitrate tetrahydrate were weighed and dissolved in 1mL of deionized water to prepare a metal salt solution. 1.0g of carbon nitride powder was then weighed and added to the metal salt solution. The solution was ultrasonically dispersed at room temperature for 30 minutes and then dried in a 60℃ oven to obtain a calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under a H2 atmosphere. The temperature was held for 6 hours and then allowed to cool naturally to obtain nickel-indium nitride. Subsequently, the temperature was increased to 400℃ at a rate of 5℃ / min under a H2 atmosphere. The temperature was held for 2 hours and then allowed to cool naturally to obtain an ordered nickel-indium alloy catalyst.
[0044] The final nickel-indium ordered alloy catalyst was analyzed using atomic-resolution spherical aberration electron microscopy. The atomic-resolution spherical aberration electron microscopy image of the nickel-indium alloy prepared by the nitrogen-mediated method in Example 4 of this application is shown below. Figure 3As shown, the nickel-indium alloy catalyst prepared in Example 4 of this application exhibits an ordered distribution of nickel and indium atoms. This result proves that the method used in Example 4 of this application can effectively synthesize an ordered nickel-indium alloy catalyst.
[0045] Example 5
[0046] This embodiment provides an ordered intermetallic compound catalyst, the preparation method of which includes: 0.291 g of nickel nitrate hexahydrate and 0.081 g of copper nitrate trihydrate were weighed and dissolved in 3 mL of deionized water to prepare a metal salt solution. 100 mg of carbon black powder was then weighed and added to the metal salt solution. After ultrasonic dispersion at room temperature for 30 minutes, the solution was dried in a 60°C oven to obtain a calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500°C at a rate of 5°C / min under an NH3 atmosphere. After holding at this temperature for 6 hours, the temperature was naturally cooled to obtain carbon-supported nickel-copper nitride. Subsequently, the NH3 gas was replaced with 10 vol% H2 / Ar gas, and the temperature was increased to 400°C at a rate of 5°C / min. After holding at this temperature for 2 hours, the temperature was naturally cooled to obtain a carbon-supported ordered nickel-copper alloy catalyst.
[0047] The final nickel-copper ordered alloy catalyst was analyzed using atomic-resolution aberration-corrected electron microscopy. The atomic-resolution aberration-corrected electron microscopy image of the carbon black-supported nickel-copper alloy prepared by the nitrogen-mediated method in Example 5 is shown below. Figure 4 As shown, the nickel-copper alloy catalyst prepared in Example 5 of this application exhibits an ordered distribution of nickel and copper atoms. This result proves that the method used in Example 5 of this application can effectively synthesize an ordered nickel-copper alloy catalyst.
[0048] Example 6
[0049] This embodiment provides an ordered intermetallic compound catalyst, the preparation method of which includes: 0.237 g of nickel chloride hexahydrate and 0.057 g of copper chloride dihydrate were weighed and dissolved in 3 mL of deionized water to prepare a metal salt solution. 100 mg of carbon black powder was then weighed and added to the metal salt solution. After ultrasonic dispersion at room temperature for 30 minutes, the solution was dried in a 60°C oven to obtain a calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500°C at a rate of 5°C / min under an NH3 atmosphere. After holding at this temperature for 6 hours, the temperature was naturally cooled to obtain carbon-supported nickel-copper nitride. Subsequently, the NH3 gas was replaced with 10 vol% H2 / Ar gas, and the temperature was increased to 400°C at a rate of 5°C / min. After holding at this temperature for 2 hours, the temperature was naturally cooled to obtain a carbon-supported ordered nickel-copper alloy catalyst.
[0050] The final nickel-copper ordered alloy catalyst was analyzed using atomic-resolution aberration-corrected electron microscopy, and the results are as follows: Figure 5 As shown, the nickel-copper alloy catalyst prepared in Example 6 of this application exhibits an ordered distribution of nickel and copper atoms. This result proves that the method used in Example 6 of this application can effectively synthesize an ordered nickel-copper alloy catalyst.
[0051] Comparative Example 1
[0052] This comparative example provides a catalyst, the preparation method of which includes: 10g of melamine was weighed and placed in a crucible, covered, and placed in a muffle furnace. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined for 4 hours. After cooling to room temperature, the resulting carbon nitride material was thoroughly ground into powder for later use. 0.291g of nickel nitrate hexahydrate and 0.081g of copper nitrate trihydrate were weighed and dissolved in 1mL of deionized water to prepare a metal salt solution. 1.0g of carbon nitride powder was then weighed and added to the metal salt solution. The solution was ultrasonically dispersed at room temperature for 30 minutes and then dried in a 60℃ oven to obtain a calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under a 10vol% H2 / Ar atmosphere. After holding at this temperature for 6 hours, it was allowed to cool naturally to obtain a disordered nickel-copper alloy catalyst.
[0053] Comparative Example 2
[0054] This comparative example provides a catalyst, the preparation method of which includes: 10g of melamine was weighed and placed in a crucible, covered, and placed in a muffle furnace. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined for 4 hours. After cooling to room temperature, the resulting carbon nitride material was thoroughly ground into powder for later use. 0.291g of nickel nitrate hexahydrate and 0.057g of silver nitrate were weighed and dissolved in 1mL of deionized water to prepare a metal salt solution. 1.0g of carbon nitride powder was then weighed and added to the metal salt solution. The solution was ultrasonically dispersed at room temperature for 30 minutes and then dried in a 60℃ oven to obtain a calcined precursor. The calcined precursor was placed in a tube furnace and heated to 500℃ at a rate of 5℃ / min under a 10vol% H2 / Ar atmosphere. After holding at this temperature for 6 hours, it was allowed to cool naturally to obtain a disordered nickel-silver alloy catalyst.
[0055] The ordered nickel-copper alloy catalyst prepared in Example 1 and the disordered nickel-copper alloy catalyst prepared in Comparative Example 1 were analyzed using atomic-resolution spherical aberration electron microscopy. The atomic-resolution spherical aberration electron microscopy image of the nickel-copper alloy prepared by the nitrogen-mediated method in Example 1 of this application is shown below. Figure 6 As shown, the atomic-level spherical aberration electron microscope image of the nickel-copper alloy prepared by the direct annealing method in Comparative Example 1 of this application is as follows. Figure 7As shown, the nickel-copper alloy catalyst prepared in Example 1 of this application exhibits an ordered distribution of nickel and copper atoms, specifically a face-centered cubic ordered structure along the
[110] zone axis. In contrast, the nickel-copper alloy catalyst prepared in Comparative Example 1 of this application exhibits a disordered distribution of nickel and copper atoms. This comparative result proves that the method used in Example 1 of this application can effectively synthesize ordered nickel-copper alloy materials.
[0056] The catalytic performance of the prepared ordered nickel-copper alloy catalyst and the disordered nickel-copper alloy catalyst prepared in Comparative Example 1 were tested.
[0057] The hydrogenation test was conducted on a flow-through fixed-bed reactor. Specifically, 100 mg of catalyst was placed in a quartz tube with an inner diameter of 5 mm, and the quartz tube was placed on the flow-through fixed-bed reactor. The reaction atmosphere was a mixture of carbon dioxide and hydrogen (gas ratio of 1:3), the pressure was 1 bar, and the reaction temperature was 400 °C. The composition of the reaction products was detected in real time by online gas chromatography. The activity graphs of the nickel-copper ordered alloy catalyst prepared in Example 1 and the nickel-copper disordered alloy catalyst prepared in Comparative Example 1 are shown below. Figure 8 As shown, when the reaction temperature is 400℃, the carbon dioxide conversion rate is 36.5%, reaching the equilibrium conversion rate, and the carbon monoxide selectivity exceeds 99%. Furthermore, its reactivity is significantly higher than that of the disordered nickel-copper alloy catalyst in Comparative Example 1. This indicates that the ordered nickel-copper alloy catalyst has significantly higher reverse water-gas shift activity than the disordered nickel-copper alloy catalyst.
[0058] The ordered nickel-silver alloy catalyst prepared in Example 2 and the disordered nickel-silver alloy catalyst prepared in Comparative Example 2 were analyzed using atomic-resolution aberration-corrected electron microscopy. The atomic-resolution aberration-corrected electron microscopy image of the nickel-silver alloy prepared by the nitrogen-mediated method in Example 2 of this application is shown below. Figure 9 As shown, the atomic-level spherical aberration electron microscope image of the nickel-silver alloy prepared by the direct annealing method in Comparative Example 2 of this application is as follows. Figure 10 As shown, the nickel-silver alloy catalyst prepared in Example 2 of this application exhibits an ordered distribution of nickel and silver atoms. In contrast, the nickel-silver alloy catalyst prepared in Comparative Example 2 of this application shows a phase-separated structure of nickel and silver atoms. This comparative result proves that the method used in Example 2 of this application can effectively synthesize an ordered nickel-silver alloy catalyst.
[0059] The catalytic performance of the prepared ordered nickel-silver alloy catalyst and the phase-separated nickel-silver alloy catalyst prepared in Comparative Example 2 were tested: The hydrogenation test was conducted on a flow-through fixed-bed reactor. Specifically, 100 mg of catalyst was placed in a quartz tube with an inner diameter of 5 mm, and the quartz tube was placed on the flow-through fixed-bed reactor. The reaction atmosphere was a mixture of carbon dioxide and hydrogen (gas ratio of 1:3), the pressure was 1 bar, and the reaction temperature was 400 °C. The composition of the reaction products was detected in real time by online gas chromatography. The activity graphs of the nickel-silver ordered alloy catalyst prepared in Example 2 and the nickel-silver disordered alloy catalyst prepared in Comparative Example 2 are shown below. Figure 11 As shown, at a reaction temperature of 400℃, the ordered nickel-silver alloy exhibited a carbon dioxide conversion rate of 11.7% and a CO selectivity close to 99%; while the disordered nickel-silver alloy in Comparative Example 2 showed a carbon dioxide conversion rate of only 5.7% and a CO selectivity of only about 10%. These results indicate that the ordered nickel-silver alloy catalyst possesses significantly higher reverse water-gas shift activity and selectivity than the disordered nickel-silver alloy.
[0060] In summary, the embodiments of this application can effectively synthesize ordered intermetallic compound catalysts, which not only have high activity, high selectivity and high stability, but also have simple preparation methods and low preparation costs, and can exhibit very high catalytic performance in the reverse water-gas shift reaction.
[0061] The above description is merely a preferred embodiment of this application, but the scope of protection of this application is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in this application, based on the technical solution and application concept of this application, should be included within the scope of protection of this application.
Claims
1. A method for preparing an ordered intermetallic compound catalyst, characterized in that, include: The first metal salt and the second metal salt are loaded onto a carrier material, and then dried and calcined to nitride, resulting in ordered intermetallic nitrides. Ordered intermetallic nitrides were subjected to low-temperature hydrogen annealing to obtain ordered intermetallic compound catalysts. The temperature for the low-temperature hydrogen annealing is between 200°C and 600°C.
2. The preparation method according to claim 1, characterized in that, The atmosphere for the low-temperature hydrogen annealing includes hydrogen. The low-temperature hydrogen annealing time is from 0.1 h to 24 h.
3. The preparation method according to claim 1, characterized in that, The calcination nitriding treatment temperature is between 200°C and 1000°C; The calcination and nitriding treatment time is from 0.1 h to 24 h; The atmosphere for the calcination and nitriding treatment includes one or both of hydrogen and ammonia.
4. The preparation method according to claim 1, characterized in that, The first metal salt and the second metal salt are each independently one or more of the following: nitrate of metal ions, chloride of metal ions, sulfate of metal ions, acetylacetone of metal ions, and acetate of metal ions.
5. The preparation method according to claim 3, characterized in that, The metal ions in the first metal salt and the metal ions in the second metal salt are each independently selected from one or more of nickel ions, cobalt ions, iron ions, copper ions, zinc ions, platinum ions, indium ions, silver ions, cadmium ions, aluminum ions, or magnesium ions.
6. The preparation method according to claim 1, characterized in that, The molar ratio of metal ions in the first metal salt to the second metal salt is (1-5):
1.
7. The preparation method according to claim 1, characterized in that, The carrier material includes one or more of carbon nitride, commercial carbon black, activated carbon, graphene, carbon nanotubes, aluminum oxide, silicon dioxide, cerium dioxide, zirconium dioxide, and titanium dioxide.
8. An ordered intermetallic compound catalyst, characterized in that, It is prepared according to the preparation method described in any one of claims 1 to 7.
9. A method for converting carbon dioxide and hydrogen into carbon monoxide, characterized in that, include: Carbon dioxide and hydrogen are reacted with water gas in the presence of a catalyst to produce carbon monoxide. The catalyst is the ordered intermetallic compound catalyst as described in claim 8 or the ordered intermetallic compound catalyst prepared according to the preparation method described in any one of claims 1 to 7.
10. The method according to claim 9, characterized in that, The temperature of the reverse water gas reaction is 200℃ to 600℃; The pressure of the reverse water gas reaction is 0.5 bar to 10 bar; The volume ratio of carbon dioxide to hydrogen is 1:(1-5).
